2021
DOI: 10.1186/s13019-021-01550-7
|View full text |Cite
|
Sign up to set email alerts
|

The effect of N-acetyl cysteine injection on renal function after coronary artery bypass graft surgery: a randomized double blind clinical trial

Abstract: Background This study aimed to compare the effects of N-acetyl cysteine on renal function after coronary artery bypass graft surgery. Methods In this randomized clinical trial conducted in Golestan Hospital, Ahvaz, Iran, 60 candidates for coronary artery bypass graft surgery were selected and divided into two N-acetyl cysteine and control groups (30 people each). Patients received 3 (2 intraoperative and 1 postoperative) doses of IV N-acetyl cystei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…However, whether AS-IV has a direct protective effect on SCs remains unclear. NAC can be used as a common antioxidant agent due to its free radical scavenging activity [ 39 ]. Therefore, we used NAC as a control to observe the therapeutic efficacy of AS-IV.…”
Section: Resultsmentioning
confidence: 99%
“…However, whether AS-IV has a direct protective effect on SCs remains unclear. NAC can be used as a common antioxidant agent due to its free radical scavenging activity [ 39 ]. Therefore, we used NAC as a control to observe the therapeutic efficacy of AS-IV.…”
Section: Resultsmentioning
confidence: 99%
“…Javaherforooshzadeh F found that administration of N-acetylcysteine can reduce the incidence of acute kidney injury in patients treated coronary artery bypass graft surgery and promoted kidney functions. 33 However, another study indicated that when evaluated in patients with stage 3 chronic kidney disease, 600 mg oral NAC supplementation was not able to alter serum creatinine or Cystatin C. 34 Lastly, there is the debate regarding NAC efficacy with kidney disease. Both SOD and CAT are antioxidant enzyme in the body.…”
Section: Discussionmentioning
confidence: 99%
“…It also shows beneficial outcomes after surgery. It was shown to decrease the incidence of acute kidney injury (AKI) after heart surgery [182] and prevented changes related to oxidative stress in routine arthroscopic knee surgery [183]. NAC ingestion followed by hyperoxia showed increased levels of erythropoietin, an effect that was not seen in the group only exposed to hyperoxia [184].…”
Section: Antioxidants and Redox Enzymesmentioning
confidence: 99%